2016
DOI: 10.1007/s40368-016-0222-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between dental caries and body mass in preschool children

Abstract: Caries prevalence in this sample of Greek children attending private day care centres was low. Overweight and obese preschool children were at higher risk of dental caries than normal- and underweight children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
1
17
2
Order By: Relevance
“…1) [Willerhausen et al, 2007;Narksawat et al, 2009;Costacurta et al, 2011;Sadeghi et al, 2011;Subramaniam and Singh, 2011;Trikaliotis Higher BMI was associated with lower odds of caries; overweight and obese children were more likely to be primary dental caries free among 7-to 9-year-olds in Guangzhou, China Elangovan et al, 2012;Norberg et al, 2012;Bagherian and Sadeghi, 2013;Shahraki et al, 2013;FriasBulhosa et al, 2015;Denloye et al, 2016;Liang et al, 2016;Pikramenou et al, 2016]. Agreement between the two reviewers was 93% for study selection and 86% for quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) [Willerhausen et al, 2007;Narksawat et al, 2009;Costacurta et al, 2011;Sadeghi et al, 2011;Subramaniam and Singh, 2011;Trikaliotis Higher BMI was associated with lower odds of caries; overweight and obese children were more likely to be primary dental caries free among 7-to 9-year-olds in Guangzhou, China Elangovan et al, 2012;Norberg et al, 2012;Bagherian and Sadeghi, 2013;Shahraki et al, 2013;FriasBulhosa et al, 2015;Denloye et al, 2016;Liang et al, 2016;Pikramenou et al, 2016]. Agreement between the two reviewers was 93% for study selection and 86% for quality assessment.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies were cross-sectional. When classifying articles according to dentition, 4 of them investigated primary dentition [Trikaliotis et al, 2011;Norberg et al, 2012;Bagherian and Sadeghi, 2013;Pikramenou et al, 2016], 6 investigated mixed dentition [Willerhausen et al, 2007;Costacurta et al, 2011;Subramaniam and Singh, 2011;Elangovan et al, 2012;Shahraki et al, 2013;Liang et al, 2016], and the remaining 4 investigated permanent dentition [Narksawat et al, 2009;Sadeghi et al, 2011;Frias-Bulhosa et al, 2015;Denloye et al, 2016]. Of the 6 studies investigating mixed dentition, 4 calculated both primary and permanent teeth [Willerhausen et al, 2007;Costacurta et al, 2011;Subramaniam and Singh, 2011;Elangovan et al, 2012], while 1 just calculated primary teeth [Liang et al, 2016] and the remaining 1 calculated permanent teeth only [Shahraki et al, 2013].…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…The association between anthropometrical measurements, mainly BMI and dental caries was examined in previous studies, and conflicting results were provided. 11,[52][53][54][55] Although underweight/ malnutrition was shown as a risk factor for dental caries in some studies 40,56 , no significant association was shown between anthropometrical measurement and caries in others. [57][58][59][60] In this study, underweight children had a slightly higher percentage of caries compared with normal counterparts whereas overweight and obese children had slightly lower.…”
Section: Discussionmentioning
confidence: 99%
“…Study from European archives of pediatric dentistry [8] showed that overweight and obese children were 1.36 times and 1.99 times more likely to be have higher caries respectively. Study from Indian Journal [9] also reported a significant association between body mass index and DMFT.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Taif University of outpatient clinic showed that 42.2% of subjects with high prevalence of dental caries were either overweight or obese [7]. A study of Thessaloniki, Greece showed that overweight children with 1.36 times and obese children with 1.99 times were more likely to have higher dmft than normal weight children [8]. A significant association between dental caries and BMI was reported in a study of Bhopal, India [9].…”
Section: Introductionmentioning
confidence: 99%